The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14814/phy2.13341
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of glucose and water drinks on blood pressure and cardiac function in older subjects with and without postprandial hypotension

Abstract: Postprandial hypotension (PPH) occurs frequently and is thought to reflect an inadequate increase in cardiac output to compensate for the rise in splanchnic blood flow after a meal. Gastric distension by water attenuates the postprandial fall in blood pressure (BP). Cardiac hemodynamics (stroke volume (SV), cardiac output (CO), and global longitudinal strain (GLS)) have hitherto not been measured in PPH. We sought to determine the comparative effects of water and glucose drinks on cardiac hemodynamics in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Indeed, blood flow is subject to complex regulation mechanisms, including autonomic and endocrine control [5], it is also possible that the final effect on systemic arterial BP of the local re-distribution of blood flow are self-limited. At this regard, some experimental data in dogs support that BP is not significantly changed after meal [1]; nonetheless, in our control group we found a slight increase in systemic arterial BP and this is in agreement with previous studies on humans that have shown a significant association between SBP/DBP in non-DM women and men [6]; this fact justifies the increase in BP during meal since it follows the insulin (INs) release. Nonetheless in a DM subjects we would expect a lower INs release during meal and, consequently, a lower increase in BP and in our case it was not.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, blood flow is subject to complex regulation mechanisms, including autonomic and endocrine control [5], it is also possible that the final effect on systemic arterial BP of the local re-distribution of blood flow are self-limited. At this regard, some experimental data in dogs support that BP is not significantly changed after meal [1]; nonetheless, in our control group we found a slight increase in systemic arterial BP and this is in agreement with previous studies on humans that have shown a significant association between SBP/DBP in non-DM women and men [6]; this fact justifies the increase in BP during meal since it follows the insulin (INs) release. Nonetheless in a DM subjects we would expect a lower INs release during meal and, consequently, a lower increase in BP and in our case it was not.…”
Section: Discussionsupporting
confidence: 93%
“…vagal efferent innervation of the pancreas). Nonetheless, compensatory cardiovascular changes following a glucose load are necessary to prevent a postprandial fall in blood pressure [33]. Therefore, communication between the cardiovascular and glucoregulatory systems is a physiological requirement, and changes in autonomic functioning within the cardiac domain represent an important component of the homeostatic response.…”
Section: Discussionmentioning
confidence: 99%
“…: 0.809 (p>0.05) [14]. Meanwhile, the results of systolic blood pressure given mineral water are in line with research conducted by Trahair et.al., where the results of the study experienced a significant increase in systolic blood pressure (p <0.05) in subjects with Postprandial Hypotension (PPH) [15]. The results of the analysis proved that by administering isotonic fluids, there was a significant reduction in heart rate on the first and second days (p<0.05), while on the third to fifth days (p>0.05) there was a decrease in heart rate but not significant, so it can be concluded that administration of isotonic fluids can cause a decrease in heart rate.…”
Section: Resultsmentioning
confidence: 84%